2020
DOI: 10.18632/aging.102682
|View full text |Cite
|
Sign up to set email alerts
|

FOXO4-DRI alleviates age-related testosterone secretion insufficiency by targeting senescent Leydig cells in aged mice

Abstract: Male late-onset hypogonadism is an age-related disease, the core mechanism of which is dysfunction of senescent Leydig cells. Recent studies have shown that elimination of senescent cells can restore proper homeostasis to aging tissue. In the present study, we found that the fork head box O (FOXO) transcription factor FOXO4 was specially expressed in human Leydig cells and that its translocation to the nucleus in the elderly was related to decreased testosterone synthesis. Using hydrogen peroxide-induced senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Recently, it has been shown that FOXO4-DRI selectively induced p53 nuclear exclusion and apoptosis in senescent Leydig cells. In naturally aged mice, FOXO4-DRI improved the testicular microenvironment and alleviated age-related testosterone secretion insufficiency (Zhang et al, 2020 ).…”
Section: Senolytics In Brain Rejuvenationmentioning
confidence: 99%
“…Recently, it has been shown that FOXO4-DRI selectively induced p53 nuclear exclusion and apoptosis in senescent Leydig cells. In naturally aged mice, FOXO4-DRI improved the testicular microenvironment and alleviated age-related testosterone secretion insufficiency (Zhang et al, 2020 ).…”
Section: Senolytics In Brain Rejuvenationmentioning
confidence: 99%
“…Again, in the first study using FOXO4-DRI to induce apoptosis in senescent cells, the senescent cells were generated by irradiation or doxorubicin ( Baar et al, 2017 ). In a recent study, FOXO4-DRI decreased levels of p53, p21, and p16 in the testes of aged mice, when compared to young mice ( Zhang et al, 2020 ). Therefore, our study and published work collectively showed that FOXO4-DRI was able to remove senescent cells created by different methods.…”
Section: Discussionmentioning
confidence: 86%
“…A relevant factor associated with late-onset hypogonadism 48 , as well as with an irreversible failure to reinstate testosterone production after critical situations that may compromise the LH-androstenedione axis is old age 49 , which has been linked to senescent dysfunction of Leydig cells 50 . The fact that a majority of non-survivor patients in our study who failed to reinstate testosterone levels are older than 60 years of age would be consistent with the senescence hypothesis.…”
Section: Discussionmentioning
confidence: 99%